2007
DOI: 10.1080/15459620701267964
|View full text |Cite
|
Sign up to set email alerts
|

Glutaraldehyde Exposures Among Workers Making Bioprosthetic Heart Valves

Abstract: Exposure to glutaraldehyde is a recognized cause of work-related asthma. An investigation was undertaken to describe exposure to glutaraldehyde among workers making bioprosthetic heart valves and to make recommendations for prevention. At the two largest heart valve manufacturing facilities in California, the work process was observed; employer representatives and glutaraldehyde-exposed workers were interviewed; and employer written records, including company-generated industrial hygiene data, were analyzed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Water et al (2003) and Cohen and Patton (2006) reported that workers exposed to glutaraldehyde at concentrations ranging from 0.4 to 1.98 mg/m 3 had associated respiratory effects. Two confirmed cases of occupational asthma attributable to glutaraldehyde were reported with exposures ranging from below the limit of detection to 3.32 mg/m 3 (Sutton et al, 2007). However, in another study reported by Teta et al (1995), where exposure levels ranged from 0.04 to 1.36 mg/m 3 of glutaraldehyde, no cases of occupational asthma were identified.…”
Section: Glutaraldehydementioning
confidence: 90%
“…Water et al (2003) and Cohen and Patton (2006) reported that workers exposed to glutaraldehyde at concentrations ranging from 0.4 to 1.98 mg/m 3 had associated respiratory effects. Two confirmed cases of occupational asthma attributable to glutaraldehyde were reported with exposures ranging from below the limit of detection to 3.32 mg/m 3 (Sutton et al, 2007). However, in another study reported by Teta et al (1995), where exposure levels ranged from 0.04 to 1.36 mg/m 3 of glutaraldehyde, no cases of occupational asthma were identified.…”
Section: Glutaraldehydementioning
confidence: 90%
“…Factors that contribute to exposure of glutaraldehyde are inadequate and unsafe working practices [17], insufficient ventilation [18], and the failure to use goggles, protective clothing and gloves [19]. …”
Section: Introductionmentioning
confidence: 99%
“…1 The Panel reviewed newly available studies since that assessment along with updated frequency and concentration of use information (Table 1). 2 46 The Panel determined to not reopen this safety assessment and confirmed the original conclusion of glutaral.…”
Section: Resultsmentioning
confidence: 90%